Casting machines in dentistry - A review part I - C Shanthi; A S Anoop; Marciano John Vialli Paul; D Narmadha; Sindhoori Harikumar; Lipsa Bhuyan (Wolters Kluwer Medknow Publications, 2024)
Dental casting machine is an electrical device used to extrude molten materials to fabricate dental prostheses such as crowns, bridges, intracoronal and extracoronal restorations, and removable partial dentures. The casting process basically include melting and casting. Firstly, the solid material is heated in a crucible in temperature-controlled conditions to melt the material to its smelled form. The dental casting process is a complex one with multifaceted steps and equipment. Different types of casting machines are available to produce heat using different sources and techniques. It includes Arc melting, Open flame casting, and Electrical resistance. Arc melting involves the application of an electric or gas discharge on tungsten electrodes, causing the metal base to melt utilizing the heat produced by arcing. Open flame casting or induction melting employs water-cooled alternate current induction coils to induce heat. However, resistance heating uses electric current to melt precious metals.